Between Prestige, Comfort, and Community: Exploring the Considerations of Padel Players in Medan City When Choosing a Court - Hafiza Adlina (Talenta Publisher, 2026)
The development of recreational sports in urban areas shows a shift in the function of sports from mere physical activity to part of a lifestyle and expression of social identity. One sport that has experienced rapid growth in major Indonesian cities is padel. This study aims to explore in depth the considerations of padel players in Medan in choosing a playing field. This study uses a qualitative approach with a phenomenological method to understand the subjective experiences and perceptions of players regarding padel courts. Data collection techniques were carried out through in-depth interviews with active padel players who play at several padel courts in the city of Medan. Data analysis was performed using thematic analysis techniques. The results of the study indicate that players' decisions in choosing a padel court are influenced by three main factors, namely the comfort of services and facilities, prestige, and the existence of community and social relations. These findings show that padel courts are not only perceived as sports facilities, but also as social spaces and symbols of urban lifestyles. This study contributes to business administration studies, particularly in understanding consumer behavior in the sports sector.